Impact of self-identity on social anxiety among college students: a moderated mediation model - Shuqi Guo; Jiazhong Yang; Shicong Zhang; Dongzhuo Xue; Mingxu Liu (Frontiers in Psychology, 2025)
BackgroundSocial anxiety is a prevalent and impairing condition among college students, often interfering with academic performance, emotional wellbeing, and social functioning.ObjectiveThis study aimed to test a moderated mediation model in which self-identity predicts social anxiety, with fear of negative evaluation (FNE) serving as a mediator and perceived social support acting as a moderator in the latter part of the pathway.MethodsA total of 328 college students (Mage = 19.48, SD = 1.02; 43.29% male) completed standardized self-report measures of self-identity, FNE, social anxiety, and perceived social support. Structural equation modeling (SEM) was used to examine the proposed model.ResultsSelf-identity significantly negatively predicted social anxiety (β = −0.55, p < 0.001). FNE partially mediated this relationship, accounting for about half of the total effect. Furthermore, perceived social support weakened the association between FNE and social anxiety under high-support conditions (moderated effect: β = −0.14, p < 0.01).ConclusionThese findings suggest the potential value of integrative intervention strategies that promote self-identity, reduce fear of negative evaluation, and enhance perceived social support to mitigate social anxiety in college populations.